Access to Justice and Legal Empowerment. Making the Poor Central in Legal Development Co-operation - van Rooij, Benjamin (Law, Governance, and Development, 2008)
Reforms to improve poor people's access to justice and to promote their legal empowerment comprise the latest trend in legal development cooperation. This volume answers a number of basic questions about this new trend, such as access to justice and legal empowerment entail and its importance; the obstacles the poor and marginalised face in seeking justice and empowerment through the legal system; and the reforms proposed by these approaches to legal development co-operation. Furthermore, it outlines important considerations for policy-makers concerning access to justice and legal empowerment reforms.